The Security and Prosperity Partnership And the Pitfalls of North American Regionalism - Alicja Gluszek (Norteamérica)
The article aims to describe in detail the essence of the Security and Prosperity Partnership (SPP), interpreting it as an initiative to overcome disfunctionalities and shortcomings of previous international arrangements among the United States, Canada, and Mexico. The SPP failed to deliver the results that its initiators had in mind; its outputs were limited in scope measured in terms of the issues tackled, joint policies, and regional regimes. It brought some policy integration into North America beyond economic issues, but did not transform itself into a regional governance mechanism that would bring about self-regulation norms and structures.